Enhancing Children's Reading Interest through the Management of Otawa Library: An Innovative Approach to Library Services - Lamatenggo, Nina; Razak, Intan Abdul; Jeni Rasdianti Olii (Jurnal Pedagogi dan Pembelajaran, 2024)
Lack of access to quality reading materials and limited opportunities to develop a reading culture are major challenges faced by foster children. This study aims to explore how the management of the Ottawa Library can increase reading interest among foster children. This study investigates how library circulation can increase reading involvement, availability of reading materials, and efforts to form a reading culture. The subjects involved in this study were the head of the library, head of sub-section, library manager, and foster children. This type of research is a case study with data collection through observation, interviews, and documentation. The data analysis process includes data collection, condensation, presentation, and drawing conclusions. The results of the study indicate that library circulation helps increase reading interest through services such as book lending, book returns, and library service hours. Reading materials in the library are quite complete, with ongoing efforts to meet the needs of foster children. In addition, the development of a reading culture is supported through collaborative programs with communities, such as the Lipu'u Pustaka community. This study recommends that the government train library staff to improve management skills, especially in circulation administration, as well as the importance of monitoring and evaluating the impact of libraries on children's reading interest. Thus, effective library management can play an important role in forming a sustainable reading culture among fostered children. The latest information in this study has implications for optimal library management to improve reading culture.